Business, Liquidity, and Information Cycles - Bostanci, Gorkem; Ordoñez, Guillermo (Quarterly Journal of Economics, 2026)
Abstract Stock markets play a dual role: they provide information about firms’ fundamentals, which improves resource allocations, and they provide liquidity. We propose a setting in which these two roles interact: if stocks are used more intensively for liquidity, then prices reveal less information about fundamentals. We structurally estimate stock price informativeness for several countries and show that it declines when alternative liquidity sources, such as banks, are in distress. To study the real effects of this mechanism, we devise a strategy to integrate our stock-trading module into a dynamic general equilibrium model with heterogeneous firms. We calibrate the model to the United States and simulate recessions with and without banking distress. In a standalone recession, prices become more informative and allocation improves, mitigating output losses by 4.4%. If the recession coincides with banking distress, agents rely more on stock markets to obtain liquidity, prices become less informative, and allocation deteriorates, magnifying output losses by 22%.